The Cambridge companion to the Trinity - Phan, Peter C., 1943- (Cambridge ; New York : : Cambridge University Press, 2011)
"How do Christians reconcile their belief in one God with the concept of three divine 'persons'? This Companion provides an overview of how the Christian doctrine of the Trinity has been understood and articulated in the last two thousand years. The Trinitarian theologies of key theologians, from the New Testament to the twentieth century, are carefully examined and the doctrine of the Trinity is brought into dialogue with non-Christian religions as well as with other Christian beliefs. Authors from a range of denominational backgrounds explore the importance of Trinitarian thought, locating the Trinity within the wider context of systematic theology. Contemporary theology has seen a widespread revival of the doctrine of the Trinity and this book incorporates the most recent developments in the scholarship"-- Provided by publish.
Includes bibliographical references and index.
Keywords: Trinity--History of doctrines